Prospective trial registration and publication rates of randomized clinical trials in digital health: A cross-sectional analysis of global trial registries. (April 2022) - Al-Durra, Mustafa; Nolan, Robert P; Seto, Emily; Cafazzo, Joseph A
Objectives: We sought to examine the prevalence of prospective registration and publication rates in digital health trials. Materials and Methods: We included 417 trials that enrolled participants in 2012 and were registered in any of the 17 WHO data provider registries. The evaluation of the prospective trial registration was based on the actual difference between the registration and enrollment dates. We identified existing publications through an automated PubMed search by every trial registration number as well as a pragmatic search in PubMed and Google based on extracted metadata from the trial registries. Results: The prospective registration and publication rates were at (38.4%) and (65.5%), respectively. We identified a statistically significant ( p < 0.001) "Selective Registration Bias" with 95.7% of trials published within a year after registration, were registered retrospectively. We reported a statistically significant relationship ( p = 0.003) between prospective registration and funding sources, with industry-funded trials having the lowest compliance with prospective registration at (14.3%). The lowest non-publication rates were in the Middle East (26.7%) and Europe (28%), and the highest were in Asia (56.5%) and the U.S. (42.5%). We found statistically significant differences ( p < 0.001) between trial location and funding sources with the highest percentage of industry-funded trials in Asia (17.4%) and the U.S. (3.3%). Conclusion: The adherence of investigators to the best practices of trial registration and result dissemination is still evolving in digital health trials. Further research is required to identify contributing factors and mitigation strategies to low compliance rate with trial publication and prospective registration in digital health trials.